Clinical evaluation of urinary basic fetoprotein and the BTA test for detection of bladder cancer - Imamura, M (Hinyokika kiyo. Acta urologica Japonica, 2000)
We compared the results of urinary basic fetoprotein (BFP) and the BTA test with those of urinary cytology in patients with bladder cancer. We also analyzed the urinary BFP and the BTA test results in patients with benign diseases and postoperative bladder cancer with no evidence of recurrence. The cutoff value for urinary BFP was set at 10 ng/ml. Classes 4 and 5 according to urinary cytology were defined as positive. The sensitivity of urinary BFP for Ta, 1 bladder cancer was significantly higher than that of urinary cytology (p < 0.05). The urinary cytology positive rate for Ta, 1 bladder cancer improved when combined with urinary BFP and the BTA test. The urinary BFP positive rate for benign diseases was significantly higher in patients with pyuria than in patients without pyuria (p < 0.05). The BTA test positive rate for benign diseases was higher in patients with pyuria than in patients without pyuria. The urinary BFP and the BTA test positive rates for postoperative bladder cancer with no evidence of recurrence was significantly higher in patients with urinary diversion than in patients without urinary diversion (BFP: p < 0.01, BTA: p < 0.05)